Almas ladinas: as muitas Áfricas de Antonio Olinto e sua contribuição ao estudo das religiões - Pimentel, Claudio Santana (2014)
This thesis discusses the contribution of literature in religious studies. For this, take the restrictions found in science of religion in relation to the overall text and literary text, and, taking arguments from post-colonials studies, rethink literature s critical-interpretative potential for religious studies. As model of relation between empirical research and literary narrative, analyses Antonio Olinto s works. This presents specificities: positioned within the generation that inaugurates Brazilian religious studies and author personal options about Catholicism and Candomblé. Olinto interprets by participatory research and literary narrative the importance of catholic festivities for the development and maintenance of an Afro-Brazilian identity in communities formed by descendants of former slaves returned from Brazil in West African cost, and the characteristics of African religious traditions. The analysis of the different genres of text aims to clarify the hermeneutic potential of literary texts, their ability to interpret religious dynamics, which should be considered for a full understanding of specific religions. Thus, it also intends to contribute to the rebuilding of a part of the history of research on religion in Brazil prior to the institutionalization of the discipline science of religion